The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares - Welter, Saskia; Bracho-Nuñez, Araceli; Mir, Celine; Zimmer, Ina; Kesselmeier, Jürgen; Lumaret, Roselyne; Schnitzler, Jörg-Peter; Staudt, Michael (Tree Physiology, 2012)
Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively. In a common garden experiment, we examined the terpene emission capacities, terpene synthase (TPS) activities and nuclear genetic markers in 52 trees of these three oak species. All but one of the Q. suber and Q. canariensis trees were found to be genetically pure, whereas most Q. afares trees possessed a mixed genotype with a predominance of Q. suber alleles. Analysis of the foliar terpene emissions and TPS activities revealed that all the Q. canariensis trees strongly produced isoprene while all the Q. suber trees were strong monoterpene producers. Quercus afares trees produced monoterpenes as well but at more variable and significantly lower rates, and with a monoterpene pattern different than that observed in Q. suber. Among 17 individuals tested, one Q. afares tree emitted only an insignificant amount of terpenes. No mixed isoprene/monoterpene emitter was detected. Our results suggest that the capacity and pattern of volatile terpene production in Algerian Q. afares populations have strongly diverged from those of its parental species and became quantitatively and qualitatively reduced, including the complete suppression of isoprene production.
10.1093/treephys/tps06910.1093/treephys/tps069
Keywords: Algerian oak; allozyme polymorphism; chemo-taxonomy; chemotype; Cork oak; isoprene synthase; isoprenoid; speciation

Why only some plants emit isoprene. - Monson, Russell K.; Jones, Ryan T.; Rosenstiel, Todd N.; Schnitzler, Jörg-Peter (Plant, cell & environment, 2012)
Isoprene (2-methyl-1,3-butadiene) is emitted from many plants and it appears to have an adaptive role in protecting leaves from abiotic stress. However, only some species emit isoprene. Isoprene emission has appeared and been lost many times independently during the evolution of plants. As an example, our phylogenetic analysis shows that isoprene emission is likely ancestral within the family Fabaceae (= Leguminosae), but that it has been lost at least 16 times and secondarily gained at least 10 times through independent evolutionary events. Within the division Pteridophyta (ferns), we conservatively estimate that isoprene emissions have been gained five times and lost two times through independent evolutionary events. Within the genus Quercus (oaks), isoprene emissions have been lost from one clade, but replaced by a novel type of light-dependent monoterpene emissions that uses the same metabolic pathways and substrates as isoprene emissions. This novel type of monoterpene emissions has appeared at least twice independently within Quercus, and has been lost from 9% of the individuals within a single population of Quercus suber. Gain and loss of gene function for isoprene synthase is possible through relatively few mutations. Thus, this trait appears frequently in lineages; but, once it appears, the time available for evolutionary radiation into environments that select for the trait is short relative to the time required for mutations capable of producing a non-functional isoprene synthase gene. The high frequency of gains and losses of the trait and its heterogeneous taxonomic distribution in plants may be explained by the relatively few mutations necessary to produce or lose the isoprene synthase gene combined with the assumption that isoprene emission is advantageous in a narrow range of environments and phenotypes.
The following values have no corresponding Zotero field: accession-num: 22998549
Keywords: Drought; ferns; phloem; phylogeny; substrate; Temperature; thermotolerance; ﬁtness

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex - Fischbach, Robert Josef; Staudt, Michael; Zimmer, Ina; Rambal, Serge; Schnitzler, Jörg-Peter (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers accession-num: 12060257
Keywords: monoterpene emissions; monoterpene synthase activities; Quercus ilex; seasonal patterns (voyant)

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.

Isolation and functional analysis of a cDNA encoding a myrcene synthase from holm oak (Quercus ilex L.) - Fischbach, Robert J.; Zimmer, Wolfgang; Schnitzler, Jörg-Peter (European Journal of Biochemistry, 2001)
An 859-bp cDNA segment of a terpene synthase gene was amplified by PCR from the evergreen sclerophyllous holm oak (Quercus ilex L.) using heterologous primers for conserved regions of terpene synthase genes (TPS) in dicotyledonous plants. Based on the sequence of this segment, homologous primers were designed for amplification by RACE-PCR of a cDNA segment carrying the monoterpene synthase gene myrS. The gene encodes a protein of 597 amino acids including an N-terminal putative plastid transit peptide. The gene without the segment encoding the transit peptide was cloned by PCR into a bacterial expression vector. Expression in Escherichia coli yielded an active monoterpene synthase, which converted geranyl diphosphate (GDP) predominantly into the acyclic monoterpene myrcene and to a very small extent into cyclic monoterpenes. Sequence comparison with previously cloned monoterpene synthases revealed that the myrcene synthase from Q. ilex belongs to the TPSb subfamily.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: functional expression; geranyl diphosphate; monoterpene synthases; myrcene synthase; Quercus ilex

Isolation and functional analysis of a cDNA encoding a myrcene synthase from holm oak (Quercus ilex L.) (European Journal of Biochemistry, 2001)
An 859-bp cDNA segment of a terpene synthase gene was amplified by PCR from the evergreen sclerophyllous holm oak (Quercus ilex L.) using heterologous primers for conserved regions of terpene synthase genes (TPS) in dicotyledonous plants. Based on the sequence of this segment, homologous primers were designed for amplification by RACE-PCR of a cDNA segment carrying the monoterpene synthase gene myrS. The gene encodes a protein of 597 amino acids including an N-terminal putative plastid transit peptide. The gene without the segment encoding the transit peptide was cloned by PCR into a bacterial expression vector. Expression in Escherichia coli yielded an active monoterpene synthase, which converted geranyl diphosphate (GDP) predominantly into the acyclic monoterpene myrcene and to a very small extent into cyclic monoterpenes. Sequence comparison with previously cloned monoterpene synthases revealed that the myrcene synthase from Q. ilex belongs to the TPSb subfamily.